CUTANEOUS MANIFESTATIONS OF CHRONIC KIDNEY DISEASE: A COMPARATIVE STUDY BETWEEN DIALYSIS AND NON-DIALYSIS PATIENTS. - Dr. Himanshu Pancheri; Dr. Abhimanyu Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Chronic Kidney Disease (CKD) is a systemic disorder that often presents with cutaneous manifestations. These skin changes can be diverse and can significantly impact the quality of life of patients. This study aims to compare the prevalence and severity of cutaneous manifestations in dialysis and non-dialysis CKD patients. A retrospective chart review was conducted to identify patients with CKD stages 3-5. Demographic data, laboratory parameters, and detailed dermatological examination findings were collected. The prevalence and severity of various skin conditions, including uremic pruritus, xerosis, calciphylaxis, and others, were compared between the two groups. The study will provide valuable insights into the cutaneous manifestations of CKD and highlight the importance of early identification and management of these conditions.